2017
DOI: 10.1111/nph.14744
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous evaluation of the effects of geographic, environmental and temporal isolation in ecotypic populations ofSolidago virgaurea

Abstract: Early stages of ecological speciation can create populations with an ecology and reproduction timing distinct from those of related populations. Landscape genetic models incorporating environmental heterogeneity and population-specific reproductive traits enable the processes of population genetic differentiation to be inferred. We investigated genome-wide genetic variation in ecotypic populations of Solidago virgaurea sensu lato, a herbaceous plant inhabiting a wide range of habitats (woodlands, serpentine ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 76 publications
1
38
1
Order By: Relevance
“…The population genetic data analysis was performed following Sakaguchi et al (2017). Principal component analysis (PCA) was applied to the whole dataset (113 individuals from 50 populations in East Asia) as a nonmodel based ordination method to extract synthetic variables, on which genetic variation between individuals is maximized.…”
Section: Population Genetic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The population genetic data analysis was performed following Sakaguchi et al (2017). Principal component analysis (PCA) was applied to the whole dataset (113 individuals from 50 populations in East Asia) as a nonmodel based ordination method to extract synthetic variables, on which genetic variation between individuals is maximized.…”
Section: Population Genetic Analysismentioning
confidence: 99%
“…Each isolated serpentine patch has a distinct combination of serpentine endemic plant species with some serpentine endemic species absent from particular patches, likely reflecting factors of dispersal limitation, past extinction events, and environmental filtering (Kitamura 1957;Mizuno et al 2009). A recent phylogeographic analysis of Solidago virgaurea L. (goldenrod; Asteraceae) revealed that the northern and southern serpentine populations showed little genetic differentiation, although they exhibited clear morphological and flowering time differentiation, while central areas were characterized by highly divergent serpentine populations (Sakaguchi et al 2017). The finding suggests that the serpentine ecotypes originated multiple times in geographically distant areas for this species.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Morphological differentiation between ecotypes (serpentine plants having smaller leaves than nonserpentine types [Figure d]) and differences in flowering time are reported (Kadota, ; Murata, ). The serpentine ecotypes do not show any qualitative differentiation in flowers and other morphological traits, and are shown to be closely related to the surrounding nonserpentine Solidago populations (Sakaguchi, Horie, Ishikawa, et al., ), making them suitable to study the adaptation and genetic interactions of populations in the process of ecotypic differentiation and possibly early stages of speciation (Sakaguchi, Kimura, et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Aoba because their seed pods dropped easily from the receptacles, and their germination rates were very low (1 and 11%, respectively in October 2016). Like Solidago virgaurea sensu lato (Sakaguchi et al 2017), a herbaceous plant inhabiting a wide range of habitats (woodlands, serpentine barrens, and alpine grasslands), remarkable variation in flowering time may promote genetic differentiation of Japanese thyme, but we speculate that Sugashima thyme keeps these traits because only Sugashima has no snow in winter (other thymes overwinter under snow over 3 months in their place of origin). Sugashima thyme has a long period for blooming and seeding, and these may be advantageous to its spread compared to vegetative propagation only.…”
Section: Discussionmentioning
confidence: 92%